Sudden Death Documented During 24-hour Holter Monitoring - Luciano, Kárila Scarduelli; Campane, Rafael Zoppi; Sales, Rafaela Louise; Kraus, Alessandra; Pestana, Erden Ramirez; Ronsoni, Rafael de March (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
A 50-year-old female patient admitted for etiological syncope investigation. A 24-hour Holter was installed where the record showed the mechanism of sudden cardiac death. Sudden bradycardia caused by paroxysmal atrioventricular block led to torsades de pointes, ventricular fibrillation and death. This case shows the importance of Holter in the chronology of arrhythmic events that lead to sudden death and highlights a poorly reported event – the occurrence of cardiac death during 24-hour Holter monitoring.